Effectiveness of antibacterial extract of coriander seeds (coriandrum sativum L.) against staphylococcus aureus - Adam M. Hamudeng; Serliawati Serliawati (DiscoverSys Inc., 2019)
Objective: Natural resources that can be used as natural antibacterial are coriandrum sativum L. which contains linalool and phenol as antibacterial ingredients.Material and Methods: Samples of bacteria were staphylococcus aureus taken from four children who had angular cheilitis. Extraction of coriandrum sativum L. using maceration method with ethanol solvent. Positive control group was given vancomycin, the treatment group was given extract of coriandrum sativum L. concentrations of 0.1%, 0.2%, 0.4%, 0.8%, 1%, 2% and 4% were incubated 24 hours. Then the inhibitory zone measurements are carried out using a caliper. Results: The results of the study showed extract concentrations of 0.1%, 0.2% and 0.4% did not show any inhibition. The concentration of 0.8% inhibition zone was only seen in the second sample (14.3 mm). The first 1% sample concentration (7.94 mm), the second sample (8.43 mm), the third sample (8.61 mm) and the fourth sample (7.77 mm). The first 2% sample concentration (8.18 mm), the second sample (8.61 mm), the third sample (8.64 mm) and the fourth sample (8.34 mm). The first 4% sample concentration (9.24 mm), the second sample (9.37 mm), the third sample (8.81 mm), and the fourth sample (8.77 mm). Vancomycin (21.3 mm) while the negative control did not show any inhibition, then the data was tested using the Kruskal Wallis and Mann Whitney Test (p<0.05).Â Conclusion: Concluded that there is a difference in inhibitory power in each treatment and the 4% concentration that is most effective in inhibiting staphylococcus aureus.